O Mito, a Mulher, a Ciranda: Lia de Itamaracá em livro-reportagem - Andrade, Marcelo Henrique (2018)
The present work has the objective of elaborating a journalistic profile about the female singer Lia de Itamaracá, an artist of popular culture in Pernambuco. The proposal is to narrate the story of the cirandeira following the concepts of Literary Journalism, elaborating important fragments of the life of Lia de Itamaracá in deep reports and gathered in a Book-Reportage. This work produced as a requirement for the title of master of the Graduate Program in Journalism, is divided into two parts: a theoretical material and the work itself, ie the book-report, as a result of an empirical research work and documentary. Within the theoretical context, one approaches the subjectivity, literary journalism, book-article, profiles, life history, popular culture and ciranda. Already the book is built within a journalistic narrative, telling the life story and artistic career of Lia, who is considered the Queen of the Ciranda and the greatest dancer in the country's life. Here are gathered narrative portraits, testimonies about the investigated character, historical data, analysis of journalistic coverage and the artist's own view of herself. In a theoretical view, the objective of this work is to understand the nuances of the journalistic profile in book-reporting, as a deepening and unfolding of the report, drawing real accounts of a living character. The idea is justified in the need to trace this life story well beyond some pages of newspaper or magazine, in a product of greater scope and space for the elaboration of a profile.